Teachers’ autonomy and innovative work behavior: the mediating role of schools’ innovation climate - Mokhlis, Safiek; Abdullah, Abdul Hakim (International Journal of Evaluation and Research in Education (IJERE), 2024)
For schools to maintain their competitiveness and enhance the standards of their education, they need to implement innovative approaches that allow them to stay abreast of the constantly changing technological, economic, and social environment. The success of these innovative approaches in schools relies heavily on teachers’ innovative work behavior (IWB), and so the role of teachers in this regard is pivotal. It is therefore crucial to determine the factors that affect teachers’ IWB. Thus, the purpose of the current study was to investigate the relationship between teachers’ autonomy, schools’ innovation climate, and IWB. A sample of teachers (n=376) from 12 primary and secondary schools in Kuala Terengganu, Malaysia, were surveyed through a questionnaire that was self-administered. Utilizing structural equation modelling with IBM AMOS version 24, schools’ innovation climate was found to have a full mediating role in the relationship between teachers’ autonomy and IWB. The findings suggest the important role of innovation climate in linking teachers’ autonomy to IWB and therefore have significant implications for school leaders.